Acoustic field characteristics of a free-piston Stirling cryocooler with large cooling capacity at liquid nitrogen temperature. (25th January 2019) - Zhu, Shunmin; Yu, Guoyao; Li, Xiaowei; Ying, Ma; Yan, Cungang; Dai, Wei; Luo, Ercang
Highlights: A free-piston Stirling cryocooler was studied from the viewpoint of acoustic field. Impact of key parameters on the acoustic field was numerically investigated. Measurement of the acoustic field was conducted to validate the calculation. The results are conducive to a better understanding and performance improvement. Abstract: A free-piston Stirling cryocooler (FPSC) with a large cooling capacity (i.e., from several hundred Watt to thousand Watt) at liquid nitrogen temperature is promising in boil-off gas recondensation and high temperature superconducting (HTS) applications. Based on thermoacoustics, this work focuses on revealing the intrinsic relationship between the internal acoustic field and cooling performance of a FPSC. The main phase shifting parameters including the moving mass of the displacer, regenerator porosity and operating frequency are systematically studied through simulation and experiment. The results indicate that the increase of displacer moving mass has limited effect on the acoustic impedance match between the cooler and the linear compressor, while the exergy loss in the regenerator will decrease dramatically due to the variation of volume flow rate therein. In contrast, the acoustic impedance match is sensitive to the regenerator porosity, and a higher regenerator porosity leads to a considerable thermal ineffectiveness loss in the regenerator and thus degrades the cooler efficiency. In addition, the acoustic field of the FPSC is strongly influenced by the operating frequency. For a fixed cooling power, a higher operating frequency causes a larger volume flow rate in the regenerator, hence the friction loss and the required acoustic power increase accordingly. Upon the analysis, experimental validation was carried out and the initial results demonstrate a reasonable agreement.